Joyce Carol Oates’s Carthage as a Modern Troilus and Cressida Story - Ruszkiewicz, Dominika (Romanica Silesiana, 2021)
Both Geoffrey Chaucer’s Troilus and Criseyde and Joyce Carol Oates’s Carthage are set in times of war, the Trojan War and the Iraq War, respectively, and both are associated with love on the one hand, and loss on the other. In fact, Carthage contains many echoes of the past, with the main characters of the novel, Juliet and Cressida Mayfield, bringing connotations with Chaucer’s and Shakespeare’s works, their father compared to an old Roman general, and Corporal Brett Kincaid likened to the hero of chivalric romances. The aim of this article is to argue that Oates’s Carthage may be seen as a modern Troilus and Cressida story in that it presents aspects of medieval reality in a modern guise, with the most poignant and recurrent association being that between the “war on terror” and medieval crusades and the emotion dominating the characters’ reactions being rage, an emotion which occurs in relation to the fires of passion and war in Chaucer’s Troilus and Criseyde, Shakespeare’s Troilus and Cressida, and Joyce Carol Oates’s Carthage.